2006
DOI: 10.1001/jama.296.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Adult Weight Change and Risk of Postmenopausal Breast Cancer

Abstract: These data suggest that weight gain during adult life, specifically since menopause, increases the risk of breast cancer among postmenopausal women, whereas weight loss after menopause is associated with a decreased risk of breast cancer. Thus, in addition to other known benefits of healthy weight, our results provide another reason for women approaching menopause to maintain or lose weight, as appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
356
0
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 556 publications
(385 citation statements)
references
References 60 publications
16
356
0
13
Order By: Relevance
“…To the best of our knowledge, no studies have been one case-control study showed that both adult weight gain before and after menopause were associated with postmenopausal breast cancer risk [13,18,34,35] whereas in one case-control study an increase in risk was only evident for adult weight gain after menopause [17]. None of these studies investigated whether these associations differed by ER/PR status of the tumor.…”
Section: Characteristics Of Studiesmentioning
confidence: 98%
“…To the best of our knowledge, no studies have been one case-control study showed that both adult weight gain before and after menopause were associated with postmenopausal breast cancer risk [13,18,34,35] whereas in one case-control study an increase in risk was only evident for adult weight gain after menopause [17]. None of these studies investigated whether these associations differed by ER/PR status of the tumor.…”
Section: Characteristics Of Studiesmentioning
confidence: 98%
“…[159][160][161] We and others have demonstrated that losing and maintaining a weight loss of ≥ 5%, either before or after the menopause, reduces post-menopausal breast cancer risk by 25-40% in the general population. [162][163][164] Weight control also appears to be important for reducing the risk of post-menopausal breast cancer among women at moderate risk with a family history with low-penetrance genetic variants (15-30% lifetime risk), 159,160,165 and among high-risk BRCA1/BRCA2 carriers (up to 60-80% lifetime risk). BMI is the only lifestyle factor that is currently incorporated into any risk model.…”
Section: Lifestyle Risk Factorsmentioning
confidence: 99%
“…Diabetes mellitus (OR 1.52, 95% CI 1.30-1.78) [30] and smoking were reported to increase the breast cancer risk [34], but not to a similar extent for all regions [35]. In contrast to reports from developed countries [36,37], a higher body mass index is not associated with premenopausal breast cancer, but is linked to postmenopausal breast cancer in Asian populations [38]. …”
Section: Risk Factorsmentioning
confidence: 99%